Pengaruh Disiplin Belajar dan Motivasi Belajar Terhadap Hasil Belajar Siswa Kelas XI pada Mata Pelajaran Ekonomi di SMA Negeri 2 Pematangsiantar T.A 2025/2026: Penelitian - Fitrianti Manurung; Sotarduga Sihombing; Benjamin Albert Simamora (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to determine the effect of learning discipline and learning motivation on the economics learning outcomes of grade XI students at SMA Negeri 2 Pematangsiantar. This study employed a quantitative approach with a descriptive method. The research population consisted of 10 classes with a total of 335 students. The sample of 89 students was selected using proportional random sampling. Data were collected through questionnaires for the variables of learning discipline and motivation, and tests as indicators of students’ learning outcomes in economics. Data analysis techniques included simple linear regression, multiple linear regression, t-test, F-test, and coefficient of determination. The results of the analysis indicated that learning discipline had a positive and significant effect on students’ learning outcomes (tcount = 3.153 > ttable = 1.987), and learning motivation also had a positive and significant effect (tcount = 5.177 > ttable = 1.987). The F-test revealed that both variables simultaneously had a significant influence on students’ learning outcomes (Fcount = 101.8 > Ftable = 3.10). The coefficient of determination (R²) of 0.61 indicated that 61% of the variation in students’ learning outcomes was influenced by learning discipline and motivation, while the remaining 39% was influenced by other factors not examined in this study.